KOMUNIKASI DALAM AL-QUR’AN: MELACAK ISTILAH KOMUNIKASI DI MEDIA SOSIAL - Dozan , Wely (LP2M IAI NURUL HAKIM, 2024)
Communication has become an important issue that never ends and is always discussed until now. Communication issues are very important, especially how the ethics of communication are good among friends, parents, even what is currently circulating is the ethics of communicating on social media. In general, the Qur'an has provided an alternative way to communicate well so as not to cause a sense of conflict and so on. The focus of this paper tries to explore several aspects as well as the formulation of the problem in this study, including, First, How is the concept of communication in the perspective of the Qur'an. Second, how to internalize communication on social media. The type of research is library research with a descriptive research approach, namely explaining various issues that are well studied through the study of relevant books, books, journals, articles and references. In particular, that the concept of communication ethics is the main capital to establish a good relationship, especially in any context that is done. The Qur'an mentions communication as one of human nature to know how humans should communicate. For example, al-bayan as the ability to communicate. In addition, the keyword used by the Qur'an for communication is to maintain something good in words, behavior, and so on. While ethics on social media is the need for more applicable knowledge about communication ethics in other social media that continues to be sustainable considering the progress of technology and information is very rapid. For the same, it does not affect the community as social media users so as not to cause concerns about the media used.